Family medicine anesthesia: Sustaining an essential service - Brown, Glenn (College of Family Physicians of Canada, 2005)
OBJECTIVE: To elicit the opinions of family physician anesthetists (FPAs) and hospital Chief Executive Officers (CEOs) regarding the structure of their organizations and the importance of family medicine anesthesia. DESIGN: Mailed survey. SETTING: Ontario hospitals. PARTICIPANTS: The CEOs of Ontario hospitals and family physicians who provide anesthetic services in Ontario hospitals. MAIN OUTCOME MEASURES: Demographics, practices, and opinions of FPAs and CEOs regarding family medicine anesthesia. RESULTS: Responses were received from 159 of 195 practising FPAs (82%). Of the 128 hospitals in Ontario that offered anesthesia services, 59% used at least one FPA; in 39% of these hospitals, all services were provided by FPAs. Both FPAs and CEOs thought that FPAs were competent to meet the anesthesia needs of small community hospitals. Most FPAs and CEOs supported certification and maintenance of competence programs coordinated by a national body, such as the College of Family Physicians of Canada. Both FPAs and CEOs thought there should be support for additional training programs in family medicine anesthesia. CONCLUSION: Small community hospitals rely completely on FPAs to provide essential anesthesia services. Additional training programs and a national structure to coordinate certification and maintenance of competence programs are important to maintain and enhance this essential service.